From Physical Spaces to Sacred Places: Spiritual Leadership in Madrasa Infrastructure Development - Pitono Pitono; Mashudi Mashudi; Abd Muhith; Amir Karimi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze how madrasah principals instill Islamic spiritual values in the development of educational facilities and infrastructure in madrasas. The study used a qualitative approach with a multi-site case study. Research data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña through the stages of data condensation, data presentation, and drawing conclusions and verification. The results show that instilling spiritual values in the development of facilities and infrastructure is carried out through three main patterns. First, integrative planning based on intention (niyyah) and Islamic values-based design thinking, namely the construction of facilities, is understood as a trust and a form of worship oriented towards benefit. Second, accountable and sharia-compliant procurement based on the values of shiddiq and amanah through transparency, responsibility, and community participation through waqf and infaq. Third, the utilization and maintenance of facilities and infrastructure based on the culture of thaharah, maslahat, and iqtishad, which emphasizes cleanliness, usefulness, and efficient use of facilities. The implications of this research indicate that the spiritual leadership of a madrasah principal can transform the management of facilities and infrastructure from a mere administrative activity into a practice of Islamic educational management that is worshipful, sustainable, and strengthens the madrasah's religious culture.